2024
DOI: 10.1109/tpwrs.2023.3262501
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Robustness-Oriented Grid Network Design for Resilience Against Multiple Hazards

Abstract: Power systems are critical infrastructure for reliable and secure electric energy delivery. Incidents are increasing, as unexpected multiple hazards ranging from natural disasters to cyberattacks threaten the security and functionality of society. Inspired by resilient ecosystems, this paper presents a resilient network design approach with an ecological robustness (R ECO )oriented optimization to improve power systems' ability to maintain a secure operating state throughout unknown hazards. The approach uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…As discussed in [23], infrastructural resilience lays the foundation for operational resilience, which provides more resources that operators and stakeholders can utilize. Recent work has shown that more robust power networks have an improved tolerance of disturbances while maintaining systems' security and resilience against hazards [16]. Likewise, a more robust communication network exhibits more paths to deliver critical information through different routes [24].…”
Section: A Cyber Physical Systems and System Of Systems Modeling And ...mentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed in [23], infrastructural resilience lays the foundation for operational resilience, which provides more resources that operators and stakeholders can utilize. Recent work has shown that more robust power networks have an improved tolerance of disturbances while maintaining systems' security and resilience against hazards [16]. Likewise, a more robust communication network exhibits more paths to deliver critical information through different routes [24].…”
Section: A Cyber Physical Systems and System Of Systems Modeling And ...mentioning
confidence: 99%
“…For example, in supply chains, the magnitude of flow between a supplier and an assembler would be equal (or proportional) to the amount of material supplied by the supplier to the assembler under normal operating conditions [42]. In an energy distribution network, the flows between any two systems would be equal (or proportional) to the planned transfer of energy between the systems under normal operating conditions [16], [45].…”
Section: B Assigning Interaction Magnitudesmentioning
confidence: 99%